Ar+ ion irradiation of magnetic tunnel junction multilayers: impact on the magnetic and electrical properties. (12th August 2020) - Teixeira, B M S; Timopheev, A A; Caçoilo, N; Cuchet, L; Mondaud, J; Childress, J R; Magalhães, S; Alves, E; Sobolev, N A
Abstract: The impact of 400 keV Ar + irradiation on the magnetic and electrical properties of in-plane magnetized magnetic tunnel junction (MTJ) stacks was investigated by ferromagnetic resonance, vibrating sample magnetometry and current-in-plane tunneling techniques. The ion fluences ranged from 10 12  c m − 2 to   5     ×     10 15  c m − 2 . Below   10 14  c m − 2, the anisotropy of the Ta-capped FeCoB free layer was weakly modulated, following a decrease in the saturation magnetization. The tunnel magnetoresistance (TMR), along with the exchange-bias and the interlayer exchange coupling providing a stable magnetic configuration to the reference layer, decreased continuously. Above 10 14  c m − 2, a strong decrease in the saturation magnetization was accompanied by a loss of the magnetic coupling and of the TMR. We show there is an ion-fluence window where the modulation of magnetic anisotropy can occur while preserving a large TMR and stable magnetic configuration of the MTJ, and demonstrate that the layers surrounding the free layer play a decisive role in determining the trend of the magnetic anisotropy modulation resulting from the irradiation. Our results provide guidance for the tailoring of MTJ parameters via ion irradiation, which we propose as a potentially suitable technique for setting the magnetic easy-cone state in MTJ for attaining field-free, fast, and non-stochastic magnetization switching.